Analisis Kadar Vitamin C Pada Jus Buah Nanas Dengan Penambahan Pemanis Alami Dan Pemanis Buatan Berdasarkan Lama Waktu Penyimpanan - Linda Sari Dwi Setyaningsih; Eka Farpina; Ganea Qorry Aina (Jurnal Sains dan Teknologi Laboratorium Medik, 2023)
Vitamin C is one of the main vitamins needed by humans every day. Pineapple fruit contains vitamin C which can be obtained through direct consumption or consumed after processing, such as into juice. Vitamin C in fruit juice may decrease with the storage time, but the decrease in vitamin C levels can be suppressed by adding sweeteners. The purpose of this study was to determine the presence and absence of differences in vitamin C levels in pineapple juice with the addition of natural sweeteners and artificial sweeteners based on the length of storage time. The type of research used is purely experimental. The study population was all pineapples harvested from pineapple plantations, Tani Bakti Village, Samboja District, Kutai Kartanegara Regency. The sample was pineapple juice made from Queen variety pineapple fruit with 4 variations of 10% concentration sweetener: sucrose, saccharin, cyclamate, and aspartame, and 1 variation of unsweetened control. With 4 variations of storage time namely 0, 30, 60, and 120 minutes. Analysis of vitamin C levels is carried out using the iodimetric titration method. The results of the study found natural sweeteners and artificial sweeteners can suppress the decrease in vitamin C levels in pineapple juice when stored. The data from the study was then carried out static tests and obtained a value of p≤0.05 which showed that there was a difference in vitamin C levels in pineapple juice with the addition of natural sweeteners sucrose and artificial sweeteners saccharin, cyclamate, and aspartame during the storage period. After further static tests were carried out and it was found that based on all storage times there was a significant difference between sucrose-sweetened fruit juice, against control fruit juice with a p-value of ≤0.05. While from pineapple fruit juice other sweeteners did not show any significant difference from control pineapple fruit juice (unsweetened).